Test pit excavation within currently occupied rural settlements in the Czech Republic, Netherlands, Poland and United Kingdom – Results of the CARE project 2020 - Lewis, Carenza; Vařeka, Pavel; van Londen, Heleen; Verspay, Johan; Marciniak, Arkadiusz; Kajda, Kornelia; Kobiałka, Dawid (Medieval Settlement Research, 2021)
A summary of the CARE project in 2020, a European project of test pit excavations in currently occupied rural settlements spanning the Netherlands, the Czech Republic, Poland and the UK.